Catalogue of the Teratomyzidae (Diptera, Opomyzoidea) of the World - Rodrigues, J.p.v.; Pereira-Colavite, A.; Mello, R.l. (Zootaxa, 2016)
A catalogue of Teratomyzidae of the world is presented comprising 23 described species in seven genera. Geographic records for nine undescribed species are also listed. All valid names and synonyms are presented, totaling 34 names. All references known to us from the taxonomic and biological literature, including information about name, author, year of publication, page number, type genus, type species, type locality and references are given to the categories of family, genus and species. Camur willii McAlpine has its distributional record enlarged to Paraná (Brazil).